Generating Hardware Assertion Checkers - Boulé, Marc (Springer, 2017)
Assertion-based design is a powerful new paradigm that is facilitating quality improvement in electronic design. Assertions are statements used to describe properties of the design (I.e., design intent), that can be included to actively check correctness throughout the design cycle and even the lifecycle of the product. With the appearance of two new languages, PSL and SVA, assertions have already started to improve verification quality and productivity.